Influence of product quality and brand image on purchasing decisions for ABC Ground coffee products in South Tangerang - Wita Andriyani (Central Research Institute for Agriculture (CeRIA), 2023)
This research aims to examine the influence of product quality and brand image on purchasing decisions for ABC ground coffee in South Tangerang. Type of associative research method with a quantitative approach, with a sample of 97 respondents and with analysis using analytical tests, namely validity test, reality test, linear regression test, correlation coefficient test, determination test, t test and f test also using the classic test, normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. Results of research carried out. Influence Product Quality on Purchasing Decisions obtained by the regression equation value Y = 12.666 + 0.683X1. hypothesis testing obtained tcount> table (8.856> 1.986). Thus ho is rejected and accepted, this shows that there is a partially positive and significant influence between Product Quality on Purchasing Decisions on ABC Ground Coffee in South Tangerang. Meanwhile, brand image on purchasing decisions obtained a regression equation value of Y = 49.423 + 0.253X2. Hypothesis testing obtained a tabet t value or ((-2.065 < 1.986). Thus Ho was rejected and H2 was accepted, this shows that there is a partially positive and significant influence between Brand Image on Purchase Decisions for ABC Ground Coffee in South Tangerang. then, the influence of Product Quality and Brand Image on Purchasing Decisions is obtained by the regression equation Y = 24.298 + 0.693 Simultaneous positive and significant influence between Product Quality and Brand Image on Purchasing Decisions on ABC Ground Coffee in South Tangerang.